Differences in Quantity and Quality of Fresh Semen and Frozen Semen After Thawing in Limousin and Simmental Cattle at Lembang Artificial Insemination Center - Ahmat, Benny; Herawati, Ervi; Rohayati, Tati; Salamah, Aisyatus (Fakultas Peternakan, Universitas Padjadjaran, 2024)
The purpose of this study was to evaluate the differences in quantity and quality of fresh semen and post-thawing frozen semen of two different cattle breeds at the Lembang Artificial Insemination Centre (BIB). The method applied in this research was case study method and used secondary data. The research material consisted of semen production records obtained from 9 Limousin cattle and 9 Simmental cattle, which were collected in July 2023 at 08.00-09.00 WIB. The variables studied were colour, volume, consistency, pH, motility, mass movement, concentration, post-thawing motility, and individual spermatozoa movement. The results showed that Limousin cattle semen had milky white (88.89%) and cream (11.11%) colour, medium consistency (55.56%) and liquid (44.44%) and mass motility value (++). While Simmental cattle semen has a milky white colour, medium consistency and mass motility value (++). The breed of cattle significantly differed on the concentration, pH of semen and post-thawing motility, then the breed of cattle had no significant difference on the volume, motility and movement of individual spermatozoa. Simmental cattle have superior semen quality compared to Limousin cattle.